INTEGRASI MULTIDISIPLINER DALAM PARADIGMA BIMBINGAN DAN KONSELING DI ERA POST-DISIPLINER - Kuswati, Lilik; Budiyanto; Evi Winingsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze multidisciplinary integration within the guidance and counseling paradigm in the post-disciplinary era. A qualitative approach employing a literature review method was used, through the examination of various relevant and current scientific literatures. The findings indicate that the development of the post-disciplinary paradigm encourages guidance and counseling to integrate various disciplines, such as psychology, education, social sciences, culture, spirituality, and technology. This integration enables a more comprehensive understanding of individuals and enhances the effectiveness of counseling services. However, its implementation faces challenges in conceptual aspects, professional competence, and ethics. Therefore, strengthening the theoretical framework and developing counselor competencies are required. This study concludes that a holistic-integrative paradigm serves as a relevant and adaptive direction for the development of guidance and counseling in the post-disciplinary era."